Effect of the CMT advanced process combined with an active cooling technique on macro and microstructural aspects of aluminum WAAM. Issue 6 (26th June 2021) - Teixeira, Felipe Ribeiro; Scotti, Fernando Matos; Reis, Ruham Pablo; Scotti, Américo
Abstract : Purpose: This paper aims to assess the combined effect of the Cold Metal Transfer (CMT) advanced process and of a thermal management technique (near immersion active cooling [NIAC]) on the macro and microstructure of Al wall-like preforms built by wire arc additive manufacturing (WAAM). As specific objective, it sought to provide information on the effects of the electrode-positive/electrode-negative (EP/EN) parameter in the CMT advanced process fundamental characteristics. Design/methodology/approach: Initially, bead-on-plate deposits were produced with different EP/EN ratios, still keeping the same deposition rate, and the outcomes on the electrical signal traces and bead formation were analyzed. In a second stage, the EP/EN parameter and the layer edge to water distance (LEWD) parameter from the NIAC technique were systematically varied and the resultant macro and microstructures compared with those formed by applying natural cooling. Findings: Constraints of EP/EN setting range were uncovered and discussed. The use of the NIAC technique favors the formation of finer grains. For a given EP/EN value, a variation in the NIAC intensity (LEWD value) showed marginal effect on grain size. When the EP/EN parameter effect is isolated, i.e. for a given LEWD setting, it was observed that an increase in the EP/EN level favors coarser grains. Originality/value: Both the EP/EN parameter and the use of an active cooling technique (NIAC) might be used, even in combination, as effective tools for achieving proper macro and microstructure in WAAM of thin wall builds.